Effect of tempering on the milling quality, pasting properties and sensory attributes of two Uruguayan long-grain rice varieties - Laura Garcia-Llobodanin; Belén Pazos; Catalina Pirotti; Agostina Rossido; Horacio Stirling; Patricia Arcia; Alejandra Billiris (Applied Food Research)
After harvesting, rice must be dried to a moisture content (MC) of around 13 % for safe storage. Drying may affect rice quality due to the formation of fissures that lead to the breakage of the kernels during milling, reducing the head rice yield (HRY). Tempering holds the kernels at the drying temperature between drying passes, reducing fissures formation. However, the exposure of rice to the drying temperature for longer periods (compared to continuous drying), may affect the sensory attributes. The aim of the present research was to study the impact of drying on the milling quality, pasting properties and sensory attributes of two Uruguayan long-grain rice varieties (Merin and Guri). To this purpose, samples were dried using different drying temperatures and tempering periods. Samples dried under very mild conditions (20 °C) were used as control. The results showed that when sufficient temperings were applied (one-hour tempering every 2 % MC reduction), it was possible to dry both varieties without reducing the HRY, using air at 55 °C and 13 % relative humidity. However, this treatment increased all the measured pasting properties of Merin and the setback of Guri, which was reflected in some sensory attributes. Reducing the amount of temperings reduced the HRY, with Merin being more affected than Guri. In conclusion, Merin was more sensitive to the drying conditions than Guri, confirming the need of specific drying programs for each variety. This would allow defining the drying conditions depending on the variety and the milling quality and sensory attributes sought.